A Citywide ‘Virus Testing': Chinese Government's Response to Preventing and Controlling the Second Outbreak of SARS-CoV-2 - Zhou, Liting; Seesaghur, Hans Nibshan; Akhtar, Nadeem; Boolakee, Jason; Pratt, Cornelius B. (Frontiers in Public Health, 2021)
Wuhan’s citywide virus-testing program presents a way forward in preventing and controlling the uncertainty, anxiety, instability and complexity it faces over the outbreak of SARS-CoV-2. Inarguably, the health crisis requires time-tested strategies and tactics for coordinating governments’ and social entities’ response to the crisis, with a goal toward having and ensuring sustained effectiveness. In the aftermath of 35 consecutive days of no new reported SARS-CoV-2 cases, six emerged on May 9, 2020, triggering additional concerns over a possible crisis of SARS-CoV-2 in Wuhan. The Prevention and Control Headquarters of Wuhan on COVID-19 launched promptly a massive virus testing of Wuhan’s 11 million residents; it was completed within 10 days. In light of this unprecedented mass testing, this study applies the situational crisis communication theory to analyze this massive virus-testing process and the mechanisms involved to contain SARS-CoV-2 in Wuhan. While many countries still have partial lockdowns, the second outbreak in Wuhan is an indication of what awaits all SARS-CoV-2-stricken countries post-lockdowns and after community restrictions have been lifted. Therefore, the recently implemented Wuhan control mechanism (in cities, districts and townships) may become a hortatory guide to other world regions as they contend with and consider appropriate measures to control the spread of SARS-CoV-2 and to protect public safety.